PELATIHAN DAN PENDIDIKAN KESEHATAN MASYARAKAT TENTANG UPAYA PENCEGAHAN FLU BURUNG DI DESA TARO GIANYAR - NLP, Suariyani; Subrata, M.; Sutarga, I M .; Kurniati, DPY,; Kardiwinata, MP.; Nopiyani, MS. (Buletin Udayana Mengabdi, 2012)
Bali as the world tourism destination will face huge impacts (economic, health and social) if there was avian influence outbreak, because tourism is a sensitive sector to the public health problems. It is therefore, an action that could increase the knowledge of community in order to prevent from the disease especially avian influences is badly in need. Taro village, Tegallalang is one of tourism destinations in Bali. In order to maintain other countries feel comfortable and secure for their citizens to visit Bali, Taro’s community in preventing diseases especially at avian influences is very crucial. Cooperation with other sectors such as education, health and others to conduct such health education is important to be able to produce good quality of program. The health education was conducted for students (SMPKerta Wisata) on 18 September 2010. The responds toward the health education program was very good, while many students ask questions about avian influences, they also could answer the entire questions already asked to the students after the programs. The questions were not asked only from the students but also from the teachers. It showed that the program was interesting for the audience. This program would improve the knowledge of community and in the future, it could be conducted in other cities in Bali.